Effect of rosemary (Rosmarinus officinalis) leaf meal supplementation on production performance and egg quality of laying hens - Kedir, Seman; Tamiru, Metekia; Tadese, Dawit; Takele, Lishan; Mulugeta, Melaku; Miresa, Ashenafi; Wamatu, Jane; Alkhtib, Ashraf; Burton, Emily (Elsevier Ltd., 2023)
This experiment was conducted to investigate the supplemental effect of rosemary leaf meal (RLM) on egg production and egg quality in Lohmann-Brown laying hens. For each treatment, six replicates were performed with four 24-week-old laying hens for a total of 96 chickens. Dried rosemary leaf meal (RLM) was present in the commercial laying hen ration at 0, 1.7, 3.5 and 5.2%, respectively. The interactions between dietary treatments, egg storage temperatures (4 ◦C, 21.5 ◦C), and egg storage durations (7, 14, 21, 28, and 35 days) were examined in factorial designs using a fully randomized design. The data were analyzed using the Statistical Analysis System (SAS, 2014, Ver. 9.3) and Tukey’s multiple range tests to separate the means. The inclusion of dried RLM at a level of 5.2% (p < 0.05) significantly improved the hens’ daily egg production (78.9%). Feed conversion ratio (2.25) and egg weight (56.7 g) compared to control treatment. Similarly, at 3.5% and 5.2% RLM supplementation, eggshell weight (5.876 g) and eggshell strength increased significantly (p < 0.05) (compared to control, a weight of 3.76 kg/ cm2 and a shell thickness (0.37 mm) was observed. In addition, the groups fed 5.2% RLM had significantly higher albumin weight (34.9 g/L), albumin height (6.9 mm), and yolk weight (15.6 g/L). l), yolk height (15.9 mm), yolk color (5.3 points), and Hough unit (83.9 points) than the control groups. Regarding the external characteristics of stored eggs, a group of hens fed at rates of 3.5 and 5.2% RLM showed significantly greater (p < 0.05) egg weight with increases in storage temperature and duration as a control group. There was a significant interaction effect between stored eggs collected from the supplemented groups in terms of egg weight, weight loss, shell weight, shell strength, and shell thickness stored at specific temperatures and storage durations. There was a decrease in albumen level and Haugh unit (HU) with an increase in storage